STRATEGI PENGEMBANGAN USAHATANI JERUK SIAM DI DESA LUBUK LEBAN KECAMATAN SOSOH BUAY RAYAP (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2016)
This study aims to analyze the development strategy of farming Tangerine in Lubuk Leban District SOSOH BUAY Termites Regency Ulu through SWOT analysis (Strength, Weakness, Opportunitie, and Threats . This research was conducted in November 2016 until January 2017 . The method used in this study is a survey method andsampling method used was stratified random method is unbalanced (Dispropotionated stratified random sampling) . The method of data processing is done using analysis matrices . Based on the result ofinternal development of citrus farming is the power (has large tracts of land for the cultivation of citrus fruit available in the fresh and health-related ) and weaknesses (harvested only once a year, farming technology is simple, using seeds local, as well as lack of maintenance) . The external factor is the development of citrus with a chance (there is always a demand , the frequency of counseling , as well as broad-scale marketing ) , and threats (competition prices , crop pests and high ) as well as strategy development citrus farming strategy that 1 )increase the production of citrus high quality with better production ,grading and standardization , and position local oranges with prestige are better than orange imports . Strategy 2 ) (3)undertakes the type of seedand cultivate citrus fruits is healthy to eat. Strategy 3 ) forms anetwork of cooperation with other stakeholders , such as largesupermarkets , networking and technology strategies must be improvedand 4 ) establish institutions related to citrus farming, more attention tothe quality of production with the implementation of Integrated Pest Management (IPM ) is right .